Losing the plot in opera myths and secrets of the world's great operas - Castles-Onion, Brian (Exisle, 2008)
The world of opera is a mystery to some and a comedy to others, but is deadly serious to the people who live and breath it. Here, opera conductor/author Brian Castles-Onion, offers light-hearted accounts of some of the best-known operas, spiced with anecdotes and behind-the-scenes gossip of the operatic world